Object-oriented and classical software engineering - Schach, Stephen R. (McGraw-Hill, 2011)
Using detailed case studies to show the object-oriented approach to software engineering, Object-Oriented and Classical Software Engineering, Eighth Edition presents an excellent introduction to software engineering fundamentals. The book covers both traditional and object-oriented techniques.